Fatores facilitadores da capacidade de inovação em subsidiária de empresa multinacional com diferentes unidades de negócios - Ribeiro, Jeferson Lima (Universidade do Vale do Rio dos Sinos, 2020)
This work deals with the factors that facilitate the capacity to generate innovations in a subsidiary of a multinational company. Based on the understanding that innovation management deals with the establishment of organizational routines and the investigation of environmental factors that affect the success of the innovation process, the purpose of this work is to contribute towards identifying these factors. For this purpose, a single case study was carried out at the company Stihl Ferramentas Motorizados Ltda., with the subsidiary's two Business Units as objects. The data were collected through document analysis, on-site observations and interviews with Managers, Directors and the company's President. From the results obtained, it was possible to identify a group of factors with the necessary potential to facilitate the process of generating the subsidiary's capacity to innovate. It was noticed that a leadership promoting the initiative, guided by the competitive strategy, added to the development and retention of knowledge and promoting a corporate culture focused on innovation are the essential ingredients to generate an innovative ‘environment’ in the context of the subsidiary. It is worth highlighting the influence of the headquarter on this environment in the sense of having an investment policy focused on R&D, by determining an adequate level of autonomy for the subsidiary and valuing and promoting the corporate culture focused on innovation.
Keywords: Fatores facilitadores; Geração de inovações; Subsidiárias; Facilitating factors; Generation of innovations; Subsidiareis; ACCNPQ::Ciências Sociais Aplicadas::Administração